Local Tax Optimization Strategy In Jambi City: A Literature Review - Nella Ervina; Syamsurijal Tan; Junaidi Junaidi; Erni Achmad (Nomico, 2024)
This scientific paper seeks to evaluate the ability of local taxation as a source of income, the level of tax participation and the efficiency of the tax collection mechanism in Jambi City budget 2018-2022. The analytical methodology used in this research includes descriptive and qualitative approaches. Descriptive analysis incorporates computational methods that are illustrated in the form of numerical data, tabulations, and graphical representations. In the meantime, the qualitative aspects include conducting intense interviews that are analyzed using SWOT. Based on the findings from the analysis of local tax effectiveness covering from 2011 to 2023, it reveals that the efficiency of local taxation shows variability in different years. Based on existing literature and comparisons between studies that have been conducted, tax optimization can be carried out in Jambi City in line with the principle of fiscal decentralization in regional autonomy by enforcing regulations to ensure the creation of sustainable development and economic growth. Some of the things that can be done are increasing tax compliance, digitalization and simplifying the tax structure. This discussion produces input to the Jambi City Government to explore the potential of local revenue, which influences the growth of Regional Own-Source Revenue (PAD). Therefore, optimal development can lead to positive outcomes for the community, such as the economic growth of people in Jambi City and the optimization of tax revenue.